Managing pressure at work - Jones, Janet; Ball, Hendrick (London : BBC Training Videos, 1991)
This video trying to manage the potential causes of stress for others, that will understand their pressure/stress levels
Narrator: Lesley Judd
Keywords: Job stress; Stress management; Strains and stresses